Menakar kedalaman pengukuran demokrasi model Indeks Demokrasi Indonesia (IDI): Beberapa catatan substantif dari Kepulauan Bangka Belitung - Ibrahim Ibrahim (Faculty of Social and Political Science, Universitas Airlangga, 2017)
Indonesian Democracy Index is one of democracy gauge in Indonesia to comprehend democratic achievement and to arrange policy program in politic development. As a measuring tool, IDI faces various methodological problems related to the representation of democratic practical circumstances in the local area. This article focuses on two aspects, methodological discourses and notes of consolidation option taken to integrate IDI output as database and political development orientation. By using qualitative method through interview,observation, documentation; this article found that there are substantive methodological problems about the technique to gather the data, distribution of data resources, difference in practical concept in understanding the data, and homogenization aspect that tend to override regional diversity with its various demographic characteristic. On the other hand, IDI faces the consolidation choice of its output in the context of dissemination and integration as an instrument in developmental planning. Without intending to delegitimize the process and consolidation option chosen by IDI, this article attempts to substantively challenge the way IDI interpret democracy and its choices about the consolidation path.